(untitled) (Nuntius Antiquus, 2014)
This text presents a free verse translation of the funeral rites (838-954) in Euripides’ The Suppliant Women. It is followed by a panoramic introduction highlighting the social function of the funeral for the war-dead. In this tragedy, Theseus fulfills the role of a commander and buries the majority of the Argive dead at Eleutherai, and it is Adrastus, along with Theseus, who conducts the funeral rites for the other five Argive heroes at Eleusis.